Comparative Study of Systemic vs. Local Antibiotics with Subgingival Instrumentation in Stage III-IV Periodontitis: A Retrospective Analysis - Ioana Ilyes; Marius Boariu; Darian Rusu; Vincenzo Iorio-Siciliano; Octavia Vela; Simina Boia; Viorelia Radulescu; Petra Șurlin; Holger Jentsch; Alexandru Lodin; Stefan-Ioan Stratul (MDPI AG, 2024)
To improve the clinical and microbiological outcomes of non-surgical mechanical periodontal therapy, the adjunctive use of antimicrobials has been utilized in treating moderate-to-severe periodontitis. In our study, the retrospective design included previously collected health-related patient data, obtained from the printed and digital charts of patients who received systemic or local antibiotic adjuncts to SI (subgingival instrumentation). A total of 34 patients (diagnosed with generalized Stage III/IV periodontitis) met the inclusion and exclusion criteria and were evaluated. The samples were tested for the following bacterial strains: Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans), Porphyromonas gingivalis (P. gingivalis), Prevotella intermedia (P. intermedia), Tanererella forsythia (T. forsythia), and Treponema denticola (T. denticola). The inter-group comparisons of the bacterial species did not show statistically significant differences between groups. The present study aimed to evaluate the clinical effects after SI and the adjunctive use of systemically administered (SA) AMX (amoxicillin) + MET (metronidazole) (administered for 7 days), with locally delivered (LDD) piperacillin + tazobactam in step 2 of periodontal therapy. Results: Overall, all parameters were improved in the groups, with a significant difference in inter-group comparison regarding the full-mouth bleeding score (FMBS) (p < 0.05) in favor of the SA group, and the p-value < 0.05 was considered to be statistically significant. Statistically significant PPD (probing pocket depth) reductions and CAL (clinical attachment level) gains were observed in both groups at the 3-month follow-up. In conclusion, within the limitations, the outcomes of this study suggest that SI, with adjunctive local or systemic antibiotic therapy, provided comparable clinical improvements. Systemic AMX + MET protocols were more efficacious with regard to the reduction in FMBS. Follow-up studies with larger patient numbers are needed to further investigate this effect.